2019
DOI: 10.1016/j.jhepr.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rituximab in difficult-to-manage autoimmune hepatitis: Results from the International Autoimmune Hepatitis Group

Abstract: Graphical abstract Highlights• Study of rituximab therapy in 22 patients with autoimmune hepatitis over a follow-up period of 24 months.• No serious adverse events were noted during followup in patients treated with rituximab.• Rituximab therapy improved liver enzymes significantly during the 2 years of follow-up.• Prednisolone dose reductions were seen in 62% of patients at 12-month follow-up.• A total of 71% of patients were free of AIH flares during the 24 months of follow-up. Lay summaryAutoimmune hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 59 publications
0
42
0
Order By: Relevance
“…28 Rituximab, a B-cell depleting agent, has been shown to induce remission in hard-to-treat AIH patients with lower complication rates. 29 Another B-cell depleting monoclonal antibody targeting the B-cell activation factor receptor is under investigation in a phase II/III trial in AIH patients who do not respond to SOC. 30 Furthermore, there is a reduced balance of regulatory and effector T cells in patients with AIH who do not achieve remission.…”
Section: Autoimmune Hepatitismentioning
confidence: 99%
“…28 Rituximab, a B-cell depleting agent, has been shown to induce remission in hard-to-treat AIH patients with lower complication rates. 29 Another B-cell depleting monoclonal antibody targeting the B-cell activation factor receptor is under investigation in a phase II/III trial in AIH patients who do not respond to SOC. 30 Furthermore, there is a reduced balance of regulatory and effector T cells in patients with AIH who do not achieve remission.…”
Section: Autoimmune Hepatitismentioning
confidence: 99%
“…Moreover, in adult AIH, rituximab treatment resulted in increased tissue and/or circulating Treg numbers. 172 Additionally, a recent report showed that rituximab could improve liver enzymes and reduce the dose of prednisone in 22 difficult-to-treat AIH patients without severe side effects, 173 which was associated with biochemical, histological and immunological remission and a significant reduction in flares in more than 70% of the patients in a two-year follow-up. 173 In PBC patients, alterations in the B cell repertoire have been observed.…”
Section: B Cell Depletionmentioning
confidence: 99%
“…172 Additionally, a recent report showed that rituximab could improve liver enzymes and reduce the dose of prednisone in 22 difficult-to-treat AIH patients without severe side effects, 173 which was associated with biochemical, histological and immunological remission and a significant reduction in flares in more than 70% of the patients in a two-year follow-up. 173 In PBC patients, alterations in the B cell repertoire have been observed. Analysis of B cell clonal diversity showed a marked reduction in clonal diversity and somatic hypermutations in class-switched sequences, which were more prominent in PBC patients with cirrhosis.…”
Section: B Cell Depletionmentioning
confidence: 99%
“…Rituximab, an anti‐CD20 monoclonal antibody, is an established therapy in autoimmune disorders and may have a role in the treatment of AIH 77‐79 . A recent retrospective report collating outcomes for 22 patients in Northern Europe and Canada demonstrated an improvement in liver biochemistry and reduction in corticosteroid doses following two 1000 mg doses of rituximab given 2 weeks apart (five patients received repeat dosing), 80 suggesting that therapeutic targeting of B cells might be a useful approach in AIH.…”
Section: Novel Therapies Undergoing Clinical Assessment In Aihmentioning
confidence: 99%